1963
DOI: 10.5134/175319
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to Japanese Ascidian Fauna. Xx. -the Outline of Japanese Ascidian Fauna as Compared With That of the Pacific Coasts of North America-

Abstract: Species common to the Japanese waters and the Pacific coasts of North America. *25. Dendrodoa pulchella *26. Pelonaia corrugata 27. Pyura mirabilis *28. Boltenia ovifera *29. Boltenia echinata *30. Halocynthia aurantium (*)31. Halocynthia hilgendorfi f. igaboja *32. Eugyrioides glutinans *33. Pareugyrioides dalli *34. Molgula griffithsii *35. Molgula retortiformis *36. Molgula pugetiensis *37. Rhizomolgula globularis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

1966
1966
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 0 publications
2
22
0
Order By: Relevance
“…The present specimen conforms well to the original description of Polyclinum saturnium given by Savigny (1816) and its subsequent one by Tokioka (1962b), especially in the colony shape, thoracic musculature and the number of stigmata! rows.…”
Section: -B)supporting
confidence: 88%
See 1 more Smart Citation
“…The present specimen conforms well to the original description of Polyclinum saturnium given by Savigny (1816) and its subsequent one by Tokioka (1962b), especially in the colony shape, thoracic musculature and the number of stigmata! rows.…”
Section: -B)supporting
confidence: 88%
“…Osaka Bay (Tokioka, 1962b), west coast of Kii Pen., 3.5 m deep (Nishikawa, 1980b) and Sagami Bay, 80 m deep (Tokioka, 1962b), Japan; Gulf of Suez (Savigny, 1816;Hartmeyer, 1915b;Michaelsen, 1920); Gulf of Aquaba (Van Name, 1952); Red Sea (Michaelsen, 1920).…”
mentioning
confidence: 99%
“…6, and this revealed that the spicules were, if present, found most frequently in the heart wall and the dorsal tubercle. The horn-shaped spicules are transparent, colorless, and cannot be dissolved in a solution of hydrochloric acid in contrast with the spicules of Herdmania momus (Savigny), that are mineralized with vaterite (CaCOa) (Lowenstam and Abbott, 1975) and Test consistency and colouration: In smaller specimens, the test is thin, soft, leathery and somewhat translucent, and milky white usually with a pinkish tint in the dorsal region, while in larger ones, it is hard, cartilaginous and generally thick, up to more than I 0 mm in thickness (though very thin, in some cases, on the attachment side), and purplish pink or, in lesser cases, pale brownish, as already noted by Tokioka (1954) …”
Section: Materials For the Present Studymentioning
confidence: 96%
“…73-75). I combined the opinions of Huus and VAN NAME and showed S. clavata as Ritterella clavata (OKA) on the list of Japanese ascidians (TOKIOKA, 1963).…”
Section: Considerationsmentioning
confidence: 99%